Can mistargeting destroy social capital and stimulate crime? Evidence from a cash transfer program in Indonesia - Lisa A. Cameron; Manisha Shah (Institute for the Study of Labor (IZA), 2012)
Cash transfer programs can provide important financial support for poor households in developing countries and are becoming increasingly common. However the potential for mistargeting of program funds is high. This paper focuses on the social consequences arising from misallocation of resources in close knit communities. We find that the mistargeting of a cash transfer program in Indonesia is significantly associated with increases in crime and declines in social capital within communities. Hence poorly administered transfer programs have a potentially large negative downside that extends beyond the pure financial costs that have been the focus of the literature to date.
Keywords: O12; O15; I38; 330; cash transfer programs; crime; mistargeting; social capital; Sozialhilfe; Wirkungsanalyse; Kriminalität; Social Capital; Gemeinschaft; Indonesien